Current Developments and Future Directions in Energy-Efficient Buildings from the Perspective of Building Construction Materials and Enclosure Systems - Rahman Azari; Ehsan Kamel; Ali M. Memari (Buildings, 2024)
The need to design buildings in compliance with the Paris Agreement goal requirements is urgent, and architects and engineers need to consider energy use and operational and embodied carbon requirements in doing so. Building envelopes will be an important element in the next generation of high-performance buildings and there have been significant advancements in recent years to develop building envelopes that help mitigate the building carbon emissions through energy-conserving low-embodied carbon or carbon-sequestering solutions. The key objective of this article is to present an overview of the state-of-the-art in the field of energy-efficient low-carbon buildings with a focus on envelope systems. This article provides a survey of the literature on energy use and carbon emissions of the United States building stock, presents recent advancements in energy-conserving building envelopes, and highlights reuse–reduce–sequester strategies that mitigate the embodied carbon of buildings. As materials are critical in reducing the energy consumption and carbon emissions of buildings, this paper also presents developments on diverse materials and building envelope solutions that have been effective in creating high-performance buildings, from insulation materials to phase-change materials and aerogels. Finally, the characteristics of a selected number of progressive net-zero-energy guidelines such as Passive House Institute (PHI) standards, Passive House Institute US (Phius) standards, the PowerHouse standard, and the BENG standard are discussed. The findings of this work highlight the increased focus on the design, construction, and engineering strategies that aim to mitigate the carbon emissions of buildings based on a holistic whole-life carbon mitigation approach.